Experimental evaluation of performance of geo-mat system on weak to intermediate subgrade - Jawad, Saif; Han, Jie; Liu, Hao (Frontiers in Built Environment, 2024)
Geo-mat system is considered as an alternative to a flexible or rigid pavement that can be used for fire lanes, parking areas, or roadway shoulders for cars, pickup trucks, utility/delivery trucks, and fire trucks. Also, it can be used to reduce the thickness of the base course in unpaved roads. In this investigation, six cyclic loading tests were conducted to assess the efficacy of the geo-mat system on weak to intermediate subgrade layers, characterized by California Bearing Ratios (CBR) of 2%, 3%, and 4%. Control sections, consisting of a 300-mm thick base course over subgrade layers with CBR values of 2% or 4%, were compared against the test sections comprising a geo-mat system layered atop aggregates of varied thickness (150 or 50 mm) on a geotextile layer over the same subgrade layers. Each test section underwent cyclic loading, progressively increasing from 17.8 to 71.2 kN using a 300-mm diameter steel plate. The results demonstrate that the geo-mat system, particularly when placed over a 150 mm-thick aggregate base, exhibited comparable or superior performance to the control sections with a 300 mm thickness, especially under substantial cyclic loading. This was evidenced by the reduced permanent deformations beneath the loading plate and a wider load distribution. The increase of the subgrade CBR value reduced the permanent deformation significantly. When the intermediate subgrade with a 4% CBR was used, the geo-mat system played a more important role than the aggregate base and the base thickness had a minor effect on the performance.